Architecture, genesis, and the sedimentary evolution model of a single sand body in tight sandstone reservoirs: A case from the Permian Shan-1–He 8 members in the northwest Ordos Basin, China - Yang, Zhen; Wang, Shumin; Chen, Jiahao; Jing, Shuai (Frontiers in Earth Science, 2023)
A single sand body is defined as a geological unit that is continuous vertically and horizontally but separated from the upper and lower sand bodies by mudstone or impermeable intercalation. The architecture of a single sand body is significant in the determination of hydrocarbon accumulation mechanisms in gas reservoirs, especially for exploitation of multiple tight sandstone gas (TSG) reservoirs. One such example is the gas reservoirs in the Tianhuan Depression, China, where the architecture and genesis of sand bodies are poorly understood. Based on the geologic background and sedimentary characteristics, the evolution of the distributary channel in the Tianhuan Depression has been examined using data from geological outcrops, cores, and well logs. The results showed that sand body architecture depends on the evolution of channel systems, and the scale and size of the channel are controlled by the sedimentary environment. Three kinds of sedimentary microfacies (distributary channel, channel mouth bar, and interdistributary bay) are mainly developed in the study area, and four types of single sand body stacking patterns (isolated, vertically superimposed, laterally tangentially superimposed, and horizontally bridged sand bodies) have formed in such a depositional environment. The target strata (Shan-1 and He-8 members) provide an ideal object for studying the evolution of the river and the architecture of the sand bodies. During the early stage of deposition, the sediment supply was insufficient, with restricted meandering river deltas dominating and sand bodies mostly existing as isolated types. Until the middle period of deposition, the sediment supply suddenly increased, the sedimentation rate accelerated with the decrease in the lake water base level, and the channel evolved into a large-scale braided river delta, generally forming superimposed sand bodies. By the late period of deposition, the provenance supply was reduced again; although braided river delta deposits were still dominant, the channel scale was restricted, and the sand bodies were predominantly isolated and horizontally bridged types. This work establishes a sedimentary evolution model for tight sandstone gas reservoirs, that is, a complete cycle of river evolution from small scale to large scale to terminal weakening, and discusses the genetic mechanism of single sand body architecture in such a depositional model.